Enzymatic kinetic resolution of racemic ibuprofen: past, present and future - José, Carla; Toledo, Victoria; Briand, Laura Estefania (Critical Reviews in Biotechnology)
This review is a journey concerning the investigations of the kinetic resolution of racemic ibuprofen for the last 20 years. The relevancy of the pharmacological uses of the S( + ) enantiomer along with its higher cost compared with racemic profen are the driving forces of a variety of scientific research studies addressing the enzymatic resolution of ibuprofen through enantiomeric esterification using lipases as biocatalysts. Lipases of fungal sources such as Candida rugosa, Rhizomucor miehei and the lipase B of Candida antarctica have been extensively studied both in homogeneous and heterogeneous (immobilized on solid supports) processes. In this context, the various alcohols and organic co-solvents frequently used in the esterification of racemic ibuprofen are summarized and discussed in this review. Moreover, recent investigations using membranes as reactors coupled with the separation of the desired product and microfluidic devices are presented. Finally, some guidelines about future perspectives regarding the technology of the kinetic resolution of profens and research niches are given. Fil: José, Carla. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas Argentina Fil: Toledo, Victoria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas Argentina Fil: Briand, Laura Estefania. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas Argentina